(untitled) (Scientific journal of the Fergana State University, 2024)
In this article, it is necessary to take into account many factors and take into account the socio-pedagogical environment and conditions when evaluating the educational achievements of students. Today, the need to modernize pedagogical measures and introduce international programs in education is increasing. The main goal of international assessment programs is to provide feedback on how students apply the knowledge they learn at school in everyday life.